Advanced Engine Management of Individual Cylinders for Control of Exhaust Species - WEST BRIAN H; PARKS JAMES E; GRAVES RONALD L; HUFF SHEAN P (2007)
This invention is a method and system for controlling engine-out exhaust species of a combustion engine having a plurality of cylinders by providing a means for controlling combustion parameters in individual cylinders, grouping the individual cylinders into a lean set and a rich set of one or more cylinders, combusting the lean set in a lean combustion parameter condition having a lean air:fuel equivalence ratio, combusting the rich set in a rich combustion parameter condition having a rich air:fuel equivalence ratio, and providing a means for adjusting the lean set and the rich set of one or more cylinders to generate net-lean combustion. The exhaust species have elevated concentrations of hydrogen and oxygen.